Parameter-Based Decision Making Under Estimation Risk: An Application to Futures Trading - Lence, Sergio H.; Hayes, Dermot J. (Journal of Finance, 1994)
This study shows how the standard portfolio model of futures trading should be modified when there is less than perfect information about the relevant parameters (estimation risk). The standard and the optimal decision rules for futures trading in the presence of estimation risk are compared and discussed. An operational model of futures trading for use under estimation risk is advanced. In the presence of relevant prior and sample information, the model can be used to optimally blend both types of information.